Melihat Konflik Jambi-Johor Dari Sudut Pandang Tungkal - Deansyah, Muhammad Rizky (Universitas Banda Naira, 2024)
Tungkal was one of the parties involved in the Jambi-Johor Conflict. The Jambi-Johor conflict was a conflict that had a major influence on the political and economic conditions of the Malacca Strait. This paper reveals Tungkal's perspective on the Jambi-Johor conflict, which indicated its impact on Tungkal's economy and trade. Through Historical research methodology consisting of Heuristics, Verification, Interpretation, and Historiography. It is known that during the Jambi-Johor Conflict, Tungkal supported Johor. After the conflict, economic and trade activities in Tungkal became quieter. The VOC's monopoly on Jambi trade, tense relations between Jambi and Johor, pirate activities, and the fall in pepper prices were the main causes of the decline.